2012
DOI: 10.1103/physrevlett.108.126405
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Quantum-Hall Liquid Spontaneously Generated by Strongly Correlatedt2gElectrons

Abstract: For topologically nontrivial and very narrow bands, Coulomb repulsion between electrons has been predicted to give rise to a spontaneous fractional quantum-Hall (FQH) state in the absence of magnetic fields. Here we show that strongly correlated electrons in a t(2g)-orbital system on a triangular lattice self-organize into a spin-chiral magnetic ordering pattern that induces precisely the required topologically nontrivial and flat bands. This behavior is very robust and does not rely on fine-tuning. In order t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 49 publications
2
106
0
Order By: Relevance
“…Interacting topological insulator [5][6][7] physics, which FCI is a time-reversal-symmetry-broken representative, is one of the major topics of the current research in the field of strongly correlated systems. FCIs have been reported in many models both for fermionic systems [2][3][4]8] and bosonic cold atom models [9][10][11][12]. Still there is no complete understanding why some model crystal systems are more convenient than others for particular FCI states.…”
Section: Introductionmentioning
confidence: 99%
“…Interacting topological insulator [5][6][7] physics, which FCI is a time-reversal-symmetry-broken representative, is one of the major topics of the current research in the field of strongly correlated systems. FCIs have been reported in many models both for fermionic systems [2][3][4]8] and bosonic cold atom models [9][10][11][12]. Still there is no complete understanding why some model crystal systems are more convenient than others for particular FCI states.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea of the TFB models is the following: (a) use a 2D lattice-based tight-binding topological-band model to mimic the nontrivial topology of a LL characterized by a nonzero Chern number [23], as first proposed by Haldane [24], and (b) find a parameter region to realize a narrow bandwidth with a smooth Berry curvature to quench the kinetic energy. These new theoretical flatband FQHE discoveries not only improve our understanding about the nature of the FQHE, but also provide us new ways to realize the FQHE in solid state materials [25][26][27][28][29] and ultracold atomic systems [14,30].…”
mentioning
confidence: 98%
“…First, the QAH state on the checkerboard lattice is actually a prominent candidates for hosting a fractional quantum-Halllike state without a magnetic field, because the topologically nontrivial band can be made almost flat by tuning hoppings and flux [21,40,41]. It turns out that even if the flux and effective hoppings t 1 and t 2 that emerge in the "umbrella" configuration do not lead to very flat bands, additional longerrange hopping −2t 3 (cos 2k x + cos 2k y ) can give a ratio of band gap vs. band width of ≈ 5 for δ = 0.3, considerably less than ratios achievable by tuning all parameters [21] or in t 2g -orbital systems [42,43], but comparable to e g [42] systems or a square-lattice model [44]. Second, it was recently demonstrated that vortex defects of the localized magnetic order underlying a QAH state can carry fractional charge and spin quantum numbers in the electronic sector [45].…”
mentioning
confidence: 99%